Silver nanowires as flexible transparent electrode: role of PVP chain length - Lau, Kam Sheng; Chin, Siew Xian; Tan, Sin Tee; Lim, Fang Sheng; Chang, Wei Sea; Yap, Chi Chin; Jumali, Mohammad Hafizuddin; Zakaria, Sarani; Chook, Soon Wei; Chia, Chin Hua (Elsevier, 2019)
In this project, crystalline silver nanowires (AgNWs) are successfully grown using a continuous segmented flow process. The robust relationship among the structural, electrical and optical properties of the AgNWs in the function of the polyvinylpyrrolidone (PVP) chain length is elaborated. A concise carrier transport and a density mechanism are also discussed using a localized conductive atomic force microscopy analysis. The obtained results proved that the AgNWs synthesized using PVP with a chain length of 1.3 M exhibit excellent electrical and optical properties in the form of flexible transparent film with a sheet resistance of <150 Ω/sq and transparency of >90% at various bending angles. These findings present an alternative approach for production of AgNWs and fabrication of a high flexible transparent electrode.